Rapid, sensitive and highly specific label-free fluorescence biosensor for microRNA by branched rolling circle amplification - Ma, Qian (2020)
A simple fluorescence biosensor for rapid and sensitive target microRNA (miRNA) quantification by branched rolling circle amplification (BRCA) is developed in this work. Target miRNA functions as primer to recognize and hybridize with a circle DNA template, initiating rolling circle amplification (RCA) by Phi29 DNA polymerase. The introduction of reverse primers complementary to the RCA products enables isothermal BRCA, in which a large amount of deoxynucleotide (dNTP) were consumed and same number of pyrophosphates (PPi) were produced. In this study, a simple and non-expensively synthesized terpyridine-based Zn(II) complex is utilized as fluorescent probe for selective detection of pyrophosphate (PPi) over dNTP. The PPi generated in this isothermal amplification process efficiently chelates to this terpyridine-Zn(II) complex, forming a highly fluorescent complex, terpyridine-Zn(II)-PPi, whose fluorescence intensity is closely related with the initial target miRNA concentration. The utilization of the isothermal BRCA amplification and direct monitoring of the DNA polymerization by-product, i.e. PPi, for non-label fluorescence detection of miRNA greatly simplify this sensor procedure. This sensor shows a linear response between the fluorescence intensity and the target miRNA concentration from 50 to 500 fM with a detection limit of 25 fM. This much-simplified sensor offers a sensitive and easy-to-use platform for miRNA quantification, and hence may significantly enhance the utilisation of miRNAs as biomarkers in drug discovery, clinical diagnosis and life science research.